Profile Enhancement Students’ Critical Thinking Skills of 7th Grade Junior High School in Natural Science Learning with Environmental Polution Subject Assisted by PODE worksheet - Dewi, Imega Syahlita; Utami, Rina Puji (Program Studi Pendidikan IPA, Universitas Islam Lamongan, 2019)
This research describes the profile of improving critical thinking skills of class VII.3 students at SMPN 4 Nganjuk in natural science learning of environmental pollution subject with the help of PODE worksheet (Predict, Observe, Discuss, Explain). Indicators of critical thinking skills assessed in this research those are: 1) Interpretation, 2) Analysis, 3) Explanation, 4) Inference, 5) Evaluation and 6) Self Regulation. The six indicators of critical thinking skill can be trained through the activities presented in the PODE worksheet. This type of research is Classroom Action Research. The method used is a pre-experimental design type One Shot Case Study, meaning that there is a group given treatment then the results are observed. The initial profile of students’ critical thinking skills before using PODE worksheet shows an unfavorable category with an average overall percentage of 40.88%. Furthermore, students’ critical thinking skills experience improvement after being given PODE worksheet which contains learning activities to train students’ critical thinking through many of problems in everyday life using successive steps starting from: Students predict problems, Students make observations with experiments, Students analyze the results of the experiment through discussion activities, and the last students explained by presentation. This is evidenced by the average acquisition of an overall percentage of 70.05% which shows a fairly good category. Thus it can be concluded that the profile of students' critical thinking skill has increased with the help of PODE worksheet.